An alternative technique for fabricating a resilient gingival mask on a three-dimensionally printed implant cast - Satyabodh Shesharaj Guttal; Pallavi Madanshetty (The Journal of Indian Prosthodontic Society)
Accurately replicating the peri-implant and pontic site soft tissues in a master cast is essential for achieving optimal contours in an implant-supported prosthesis. An implant cast with soft tissue replication allows for seamless integration of the prosthesis with the natural oral anatomy, resulting in an ideal emergence profile and improved esthetics. Furthermore, it encourages proper oral hygiene, leading to improved overall gingival health. A flexible gingival mask is used for this purpose. There are well-established methods for fabricating these masks on dental stone casts in an analog method. On the other hand, there is only one method currently being used to fabricate gingival masks on three-dimensional (3D) printed implant casts, which is both labor intensive and time consuming. Therefore, the purpose of this article is to provide a quicker and more effective method for creating gingival masks for 3D printed implant casts.